2017
DOI: 10.1016/j.dsx.2016.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between plasma osteocalcin, glycaemic control and components of metabolic syndrome in adult Nigerians with type 2 diabetes mellitus

Abstract: Plasma osteocalcin levels are inversely associated with good glycaemic control and components of MetS and are lower in individuals with DM and in those with MetS. These findings support a vital role of the bone, in the regulation of glucose and energy metabolism, in Nigerians. Further extensive studies are required to explore the potentials of OC in the management of DM and MetS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Given that the serum levels of osteocalcin differ between sexes and alter with age, the relationship of serum osteocalcin levels with CVD risk may also differ according to these variables ( 37 ). Studies have demonstrated that close correlations of serum osteocalcin level with glucose and lipid metabolic disorders, obesity, and MetS ( 8 , 38 ). Herein, the serum N-MID level was correlated with CRP, FBG, HbA1C, HDL-C, and TG after adjusting for age and sex.…”
Section: Discussionmentioning
confidence: 99%
“…Given that the serum levels of osteocalcin differ between sexes and alter with age, the relationship of serum osteocalcin levels with CVD risk may also differ according to these variables ( 37 ). Studies have demonstrated that close correlations of serum osteocalcin level with glucose and lipid metabolic disorders, obesity, and MetS ( 8 , 38 ). Herein, the serum N-MID level was correlated with CRP, FBG, HbA1C, HDL-C, and TG after adjusting for age and sex.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, the prevalence of MetS was estimated based on the IDF and/or NCEP-ATP III 2004 criteria. Among the articles, eleven studies reported the prevalence of MetS based on both NCEP-ATP III 2004 and IDF criteria [ 33 , 39 41 , 44 46 , 49 , 50 , 52 , 54 ], fourteen studies reported based solely on NCEP-ATP III 2004 criteria [ 26 , 27 , 29 32 , 34 , 36 , 37 , 42 , 43 , 47 , 51 , 53 ], and five studies reported based on IDF criteria alone [ 25 , 28 , 35 , 38 , 48 ]. Additionally, nine studies reported the prevalence of MetS subcomponents based on NCEP-ATP III 2004 criteria [ 26 , 27 , 32 , 36 , 41 45 ] and six studies based on IDF criteria [ 25 , 28 , 41 , 44 , 45 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…The role of OCN in glucose and energy metabolism was also shown in several cross-sectional and observational studies in humans, indicating inverse relation of total OCN (tOCN) and/or uOCN with fasting blood glucose (FBG), fasting insulin, homeostasis model assessment of insulin resistance (HOMA-IR) index, and adiposity; however, a positive correlation of OCN with serum adiponectin and insulin secretion was observed in non-diabetic, pre-diabetic, and diabetic populations (8)(9)(10).…”
Section: Introductionmentioning
confidence: 81%